Effective human relations - Reece, Barry L. (Houghton Mifflin, 2008)
This comprehensive text covers the key human relation skills students need to be successful managers in the workplace. Ideal for both two- and four-year programs, Effective Human Relations uses an organizational perspective to help students understand the disparate factors that influence employee behavior. The Tenth Edition focuses more directly on chapter objectives, establishing them around the seven themes of the text--communication, self-awareness, self-acceptance, motivation, trust, self-disclosure, and conflict resolution--so that the students absorb and connect the concepts. New areas of coverage include goal-setting principles; root causes of negative attitudes; introduction of the Reiss Profile instrument used to classify our basic desires; the use of "branding" to achieve greater visibility in a crowded job market; discrimination based on a person's religious preference; new ways to classify various forms of technostress; and new support for the importance of emotional intelligence. Throughout the text, major themes are supported by a multitude of real-world examples and emotional intelligence checkpoints